Skrining Fitokimia dan Penetapan Kadar Flavonoid Total Ekstrak Etanol 96% Daun Bangkal (Nauclea subdita (Korth.) Steud) - M. Hidayatullah; M. Andi Chandra; Sofi Azzahro (Jurnal Kesehatan Islam : Islamic Health Journal, 2023)
Abstract. The Bangkal plant (Nauclea subdita (Korth.) Steud.) has benefits as a natural ingredient that can treat wounds, and is applied to boils, tumors, boiled water from Bangkal leaves for diarrhea, and cures toothache. Compounds that have the potential to produce these effects are flavonoids. Flavonoids are important substances in plants, these substances help maintain plant health and are able to protect humans from disease. This study aims to determine the content of secondary metabolites and total flavonoids content of 96% ethanol extract of Bangkal leaves originating from the Astambul region, South Kalimantan using UV-Vis spectrophotometry. Extraction of Bangkal leaves was carried out by maceration method using 96% ethanol solvent, then phytochemical screening was carried out with 5 secondary metabolites and testing for total flavonoid content with AlCl3 reagent. The results showed that the 96% ethanol extract of Bangkal leaves had a yield of 14.70%, secondary metabolites which contained flavonoids, triterpenoids and tannins. The total flavonoid content was 21.508 mgQE/g. In conclusion, the 96% ethanol extract of Bangkal leaves contains high levels of flavonoids